Comprehensive Analysis of the 5xFAD Mouse Model of Alzheimer’s Disease Using dMRI, Immunohistochemistry, and Neuronal and Glial Functional Metabolic Mapping - Emil W. Westi; Saba Molhemi; Caroline Termøhlen Hansen; Christian Stald Skoven; Rasmus West Knopper; Dashne Amein Ahmad; Maja B. Rindshøj; Aishat O. Ameen; Brian Hansen; Kristi A. Kohlmeier; Blanca I. Aldana (Biomolecules, 2024)
Alzheimer’s disease (AD) is characterized by complex interactions between neuropathological markers, metabolic dysregulation, and structural brain changes. In this study, we utilized a multimodal approach, combining immunohistochemistry, functional metabolic mapping, and microstructure sensitive diffusion MRI (dMRI) to progressively investigate these interactions in the 5xFAD mouse model of AD. Our analysis revealed age-dependent and region-specific accumulation of key AD markers, including amyloid-beta (Aβ), GFAP, and IBA1, with significant differences observed between the hippocampal formation and upper and lower regions of the cortex by 6 months of age. Functional metabolic mapping validated localized disruptions in energy metabolism, with glucose hypometabolism in the hippocampus and impaired astrocytic metabolism in the cortex. Notably, increased cortical glutaminolysis suggested a shift in microglial metabolism, reflecting an adaptive response to neuroinflammatory processes. While dMRI showed no significant microstructural differences between 5xFAD and wild-type controls, the study highlights the importance of metabolic alterations as critical events in AD pathology. These findings emphasize the need for targeted therapeutic strategies addressing specific metabolic disturbances and underscore the potential of integrating advanced imaging with metabolic and molecular analyses to advance our understanding of AD progression.